Use of anion clay hydrotalcite to remove coloured organics from aqueous solutions / Yamin Yasin, Lim Ying Chin and Lim Ying Siew - Yasin, Yamin; Lim, Ying Chin; Lim, Ying Siew (2006)
Hydrotalcite was synthesized using co-precipitation method. The resulting hydrotalcite was used as an adsorbent for removal of methylene blue dye and humic acid from aqueous solution. The colour change of methylene blue dye and humic acid were used as an indicator to measure the amount of methylene blue and humic acid being adsorbed. Various parameters affecting the adsorption process were studied. These include contact time, adsorbent dosage, initial concentrations and temperature. Characterization of the resulting sample was done using Powder X-Ray diffraction analysis and Fourier Transform Infrared analysis. X-Ray diffractogram of the samples synthesized showed the presence of sharp peaks which signifying high crystallinity. The basal spacing corresponding to the 003 reflection was found to be 9.7A. The spectra of HT prepared showed OH stretching and OH bonding around 3200-3800 cm'1 and 1400-1600 cm"1, respectively. Adsorption kinetics of both of the adsorption studied showed that hydrotalcite is better adsorbent to remove colour of organic solutions. Percentage uptake increased with increased contact time, adsorbent dosage, initial concentration and temperature used.